Correlation Between Work Experience and Nurses' Competence in Performing Nursing Interventions - Jenita Oktavia Panjaitan; Karl Frizts Pasaribu (CV. Get Press Indonesia, 2025)
Work experience is a crucial aspect in improving the skills and effectiveness of nurses in carrying out nursing actions. Nurses with longer experience tend to have better competence in clinical decision making and implementing optimal nursing care. However, variations in ability due to work experience still exist, so further research is needed. This study aims to analyze the relationship between work experience and the ability of nurses in carrying out nursing actions at Hospital X. Using a cross-sectional design with a quantitative approach, this study involved 120 inpatient nurses selected through proportional random sampling techniques. Data were collected using a questionnaire that had been tested for validity and reliability, then analyzed univariately and bivariately using the Spearman test. The results showed that 70.8% of nurses had high work experience, 29.2% moderate, and none were low. In terms of ability, 65% of nurses were categorized as good, 31.7% sufficient, and 3.3% lacking. The Spearman test showed a significant and strong relationship (p = 0.000; r = 0.712) between work experience and nurse ability. This means that the higher the work experience, the better the nurse's ability. It is recommended that hospitals develop ongoing training, supervision, and mentoring programs to improve the competency of nurses with lower work experience. Thus, the quality of nursing services can be continuously improved to support patient safety and satisfaction.